Airborne particles in the city center of Kuala Lumpur: Origin, potential driving factors, and deposition flux in human respiratory airways - Khan M.F.; Hamid A.H.; Bari M.A.; Tajudin A.B.A.; Latif M.T.; Nadzir M.S.M.; Sahani M.; Wahab M.I.A.; Yusup Y.; Maulud K.N.A.; Yusoff M.F.; Amin N.; et al. (Elsevier B.V., 2023)
Deposition rates; Industrial emissions; Particle size; Particles (particulate matter); Respiratory system; Shape memory effect; Size distribution; Correlation analysis; Deposition modeling; Human respiratory system; Meteorological factors; Particle number concentration; Potential deposition; Scanning mobility particle sizer; Urban air pollution; Air pollution control; atmospheric deposition; concentration (composition); particulate flux; particulate matter; size distribution; urban area; adult; air pollution; airborne particle; article; concentration (parameters); correlation analysis; Federal Territory of Kuala Lumpur; female; human; Indian Ocean; male; meteorological phenomena; particle size; upper respiratory tract; air pollutant; air pollution; analysis; city; environmental monitoring; exposure; Malaysia; particulate matter; respiratory system; statistics and numerical data; Kuala Lumpur [Kuala Lumpur (ADS)]; Kuala Lumpur [West Malaysia]; Malaysia; West Malaysia; Air Pollutants; Air Pollution; Cities; Environmental Monitoring; Humans; Inhalation Exposure; Malaysia; Meteorological Concepts; Particulate Matter; Respiratory System